APPLICATIONS OF CHEMICALLY SYNTHESIZED CUS: PBO ALLOYED THIN FILMS IN MULTILAYER SOLAR CELLS AND OPTOELECTRONICS - Onwuemeka, Joseph Ijeoma; Ebosie, Ngozi Patricia; Anumaka, Michael Chukwukadibia; Enedoh, Margaret Chinyelu (International Journal of Engineering Technologies and Management Research, 2018)
CuS: PbO, alloyed thin films were successfully deposited on glass substrates under the deposition condition of 40oC of NaOH solution, using two solution based methods: successive ionic layer adsorption and reaction (SILAR) and solution growth technique. The crystallographic studies were done using X-ray diffractometer (XRD) and scanning electron microscope (SEM). The deposited alloyed samples were annealed at 250oC and 1500C. using Master Chef Annealing Machine. Rutherford backscattering Spectroscopy (RBS) analysis confirmed the percentage of the elements of copper, lead, sulphur and oxygen in the alloyed thin films. The optical characterization was carried out using UV-1800 double beam spectrophotometer. Sample cp1 annealed at 250 oC has an optical transmittance of 27% -71% in the ultraviolet region, 71%-83% in the visible and 83%-88% in the near infrared regions of electromagnetic spectrum. The alloyed thin films of samples cp2 of CuS:PbO annealed at 150oC, show optical transmittance of 15%-61% in the ultraviolet region, 61%-59% in the visible, and becomes linear through the near-infrared regions of electromagnetic spectrum. The two samples, have equal direct wide band gap of 3.65±0.05eV. From the spectral qualities, these compounds alloyed thin films may found useful in passive layer in heat and cold mirror application, vulcanization in tyre production due its thermal stability, active multilayer in various types of solar cells, liquid crystal displays, flat panel displays for optoelectronic applications and gas censor applications.